Internal disinhibition predicts 5‐year weight regain in the National Weight Control Registry (NWCR) - J. Lillis; J. G. Thomas; H. Niemeier; R. R. Wing (Wiley, 2016)
Summary Background Maintenance of weight loss remains elusive for most individuals. One potential innovative target is internal disinhibition (ID) or the tendency to eat in response to negative thoughts, feelings or physical sensations. Individuals high on ID do worse on average in standard behavioural treatment programmes, and recent studies suggest that disinhibition could play a significant role in weight regain. Purpose The purpose of the current study was to examine whether ID was associated with weight change over 5 years of follow‐up in the National Weight Control Registry, a registry of individuals who have successfully lost weight and maintained it. Methods From the National Weight Control Registry, 5,320 participants were examined across 5 years. Weight data were gathered annually. The disinhibition subscale of the Eating Inventory was used to calculate internal disinhibition and External Disinhibition (ED) and was collected at baseline, year 1, year 3 and year 5. Linear mixed models were used to estimate the weight loss maintained across follow‐up years 1 to 5 using ID and ED as baseline and prospective predictors. Results Internal disinhibition predicted weight regain in all analyses. ED interacted with ID, such that individuals who were high on ID showed greater weight regain if they were also higher on ED. Conclusions The ID scale could be a useful screening measure for risk of weight regain, given its brevity. Improved psychological coping could be a useful target for maintenance or booster interventions.